Uso cotidiano y pedagógico de las TIC por profesores de una universidad privada de Lima - Chumpitaz Campos, Lucrecia (2012)
Daily and Educational use of Information and Communication Technology by teachers at a private university in Lima In the context of higher education as opposed to scholar levels, urges further studies delineate clear guidelines to promote the educational integration of Information and Communication Technologies (ICT) in a relevant way on university. This article presents the results of a descriptive study of the everyday uses of technology by the lecturers of different faculties of a university. It also presents the data relating to educational use of the resources on a daily basis, they used them to develop on their classes. It identifies a clear reduction in the use of technological resources uses daily in their roles as teachers. In that sense is perceived a repeated use of resources such as Power point presentations, finding information on the Internet and the use of video mainly. Beyond that, there is not an effective integration in ICT resources in the educational development even though university has a virtual platform. This study was conducted with lecturers from all departments of the university through a further survey and focus group was conducted supplemented in the information gathered by the survey. We report the synthesis of the results of this study and recommendations to guide policy processes and training teachers in the use of such resources in their teaching.